A new species of Meriania (Melastomataceae) with remarkably small flowers from northern Peru - Fernandez-Hilario, Robin; Goldenberg, Renato; Michelangeli, Fabián A. (Phytotaxa, 2020)
Meriania microflora (Merianieae, Melastomataceae), a new species endemic to the Amazonas-Loreto border, in the Peruvian Amazon, is described and illustrated here. The new species presents the smallest flowers recorded within the genus, and also differs from other species of Meriania by the combination of appendages on the petioles, white petals, strongly dimorphic stamens and connectives with developed ascending appendages and multilobed descending appendages.